A novel application of 2-silylated 1,3-dithiolanes for the synthesis of aryl/hetaryl-substituted ethenes and dibenzofulvenes - Mlostoń, Grzegorz; Pipiak, Paulina; Hamera-Fałdyga, Róża; Heimgartner, Heinz (Beilstein Journal of Organic Chemistry, 2017)
Trimethylsilyldiazomethane (TMS-CHN2) reacts readily with hetaryl thioketones to give sterically crowded 2-trimethylsilyl-4,4,5,5-tetrahetaryl-1,3-dithiolanes with complete regioselectivity at −75 °C as well as at rt. Thiofluorenone, a relatively stable and highly reactive aryl thioketone, yields upon treatment with TMS-CHN2 at −60 °C the corresponding 1,3,4-thiadiazoline. This unstable cycloadduct undergoes decomposition at ca. −45 °C and the silylated thiocarbonyl S-methanide generated thereby is trapped with complete regioselectivity by aryl or hetaryl thioketones forming also sterically crowded 2-trimethylsilyl-1,3-dithiolanes. The obtained 1,3-dithiolanes, by treatment with an equimolar amount of TBAF in a one-pot procedure, are converted in high yields into hetaryl/aryl-substituted ethenes or dibenzofulvenes, respectively, via a cycloreversion reaction of the intermediate 1,3-dithiolane carbanion. The presented protocol offers a new, highly efficient approach to tetrasubstituted ethenes and dibenzofulvenes bearing aryl and/or hetaryl substituents.
Keywords: diazomethanes; 1,3-dipolar cycloadditions; olefination reactions; reaction mechanisms; thioketones

(untitled) - Suzuki, T.; Shiohara, H.; Monobe, M.; Sakimura, T.; Tanaka, S.; Yamashita, Y.; Miyashi, T. (Angew. Chem., Int. Ed. Engl., 1992)

(untitled) - Fischer, E.; Larsen, J.; Christensen, J. B.; Fourmigué, M.; Madsen, H. G.; Harrit, N. (J. Org. Chem., 1996)

(untitled) - Bolzoni, A.; Viglianti, L.; Bossi, A.; Mussini, P. R.; Canteruccio, S.; Baldoli, C.; Licandro, E. (Eur. J. Org. Chem., 2013)

(untitled) - Zhang, G.-F.; Wang, H.; Aldred, M. P.; Chen, T.; Chen, Z.-Q.; Meng, X.; Zhu, M.-Q. (Chem. Mater., 2014)

(untitled) - Yamamoto, A.; Matsui, Y.; Asada, T.; Kumeda, M.; Takagi, K.; Suenaga, Y.; Nagae, K.; Ohta, E.; Sato, H.; Koseki, S.; Naito, H.; Ikeda, H. (J. Org. Chem., 2016)

Cross Conjugation: Modern Dendralene, Radialene and Fulvene Chemistry - Hopf, H.; Sherburn, M. S. (Wiley VCH Verlag GmbH, 2016)

(untitled) - Shimizu, M.; Nagao, I.; Kiyomoto, S.-i.; Hiyama, T. (Aust. J. Chem., 2012)

(untitled) - Gopikrishna, P.; Iyer, P. K. (J. Phys. Chem. C, 2016)

(untitled) - Krygowski, T. M.; Szatylowicz, H.; Stasyuk, O. A.; Dominikowska, J.; Palusiak, M. (Chem. Rev., 2014)

(untitled) - Maryanoff, B. E.; Reitz, A. B. (Chem. Rev., 1989)

(untitled) - Blakemore, P. R. (J. Chem. Soc., Perkin Trans. 1, 2002)

(untitled) - van Staden, L. F.; Gravestock, D.; Ager, D. J. (Chem. Soc. Rev., 2002)

(untitled) - Fustero, S.; Simón-Fuentes, A.; Barrio, P.; Haufe, G. (Chem. Rev., 2015)

(untitled) - Fürstner, A.; Bogdanović, B. (Angew. Chem., Int. Ed. Engl., 1996)

(untitled) - Barton, D. H. R.; Guziec, F. S., Jr; Shahak, I. (J. Chem. Soc., Perkin Trans. 1, 1974)

(untitled) - Guziec, F. S., Jr; Sanfilippo, L. J. (Tetrahedron, 1988)

Targets in Heterocyclic Systems - Mlostoń, G.; Heimgartner, H. (Italian Chemical Society, 2005)

(untitled) - Mlostoń, G.; Grzelak, P.; Hamera-Fałdyga, R.; Jasiński, M.; Pipiak, P.; Urbaniak, K.; Albrecht, Ł.; Hejmanowska, J.; Heimgartner, H. (Phosphorus, Sulfur Silicon Relat. Elem., 2017)

(untitled) - Mlostoń, G.; Huisgen, R. (Heterocycles, 1985)

(untitled) - Mlostoń, G.; Urbaniak, K.; Linden, A.; Heimgartner, H. (Helv. Chim. Acta, 2015)

(untitled) - McKee, M. L.; Mlostoń, G.; Urbaniak, K.; Heimgartner, H. (Beilstein J. Org. Chem., 2017)

(untitled) - Mlostoń, G.; Pipiak, P.; Heimgartner, H. (Beilstein J. Org. Chem., 2016)

(untitled) - Mlostoń, G.; Urbaniak, K.; Linden, A.; Heimgartner, H. (Pol. J. Chem., 2007)

(untitled) - Degl’Innocenti, A.; Capperucci, A.; Nocentini, T. (Tetrahedron Lett., 2001)

(untitled) - Capperucci, A.; Cerè, V.; Degl’Innocenti, A.; Nocentini, T.; Pollicino, S. (Synlett, 2002)

(untitled) - Rele, S.; Talukdar, S.; Banerji, A.; Chattopadhyay, S. (J. Org. Chem., 2001)

(untitled) - Gröbel, B.-T.; Seebach, D. (Synthesis, 1977)

(untitled) - Eymur, S.; Göllü, M.; Tanyeli, C. (Turk. J. Chem., 2013)

Science of Synthesis - Leung, M.-K.; Luh, T.-Y. (Product Subclass 3: 1,3-Dithiolanes, 2007)

Protective Groups in Organic Synthesis - Green, T. W.; Wuts, P. G. M. (Wiley-Interscience, 1999)
pp 329–344 and pp 724–727.

Book of abstracts of XIX International Symposium - Pipiak, P.; Mlostoń, G.; Glatthor, J.; Mitzel, N. W. (Advances in the Chemistry of Heteroorganic Compounds, Łódź, 25.11.2016)

(untitled) - Hamera-Fałdyga, R.; Grzelak, P.; Pipiak, P.; Mlostoń, G. (Phosphorus, Sulfur Silicon Relat. Elem., 2017)

(untitled) - Campaigne, E.; Reid, W. B., Jr (J. Am. Chem. Soc., 1946)

(untitled) - Mlostoń, G.; Urbaniak, K.; Gębicki, K.; Grzelak, P.; Heimgartner, H. (Heteroat. Chem., 2014)

(untitled) - Tongco, E. C.; Wang, Q.; Prakash, G. K. S. (Synth. Commun., 1997)

(untitled) - Vicha, R.; Rouchal, M.; Kozubková, Z.; Kuřitka, I.; Marek, R.; Branná, P.; Čmelik, R. (Supramol. Chem., 2011)